SMEs Performance During Covid-19 Pandemic and VUCA Era: How the role of Organizational Citizenship Behavior, Budgetary, Participation and Information Asymmetry? - Setyoko, Paulus Israwan; Kurniasih, Denok (International Journal of Social and Management Studies, 2022)
The purpose of this study was to identify the effect of organizational citizenship behavior (OCB), budgetary, participation and information asymmetry on SMEs Performance During the Covid-19 Pandemic and VUCA Era. This research method is quantitative through online surveys through online social media. The sampling technique used was purposive sampling technique with the specified number of samples as many as 190 SMES management respondents. The quantitative data analysis technique used partial least square structural equation modeling (PLS-SEM) analysis. Based on the results of calculations using PLS-SEM software version 3.0, the results show that there is not significant relationship between organizational citizenship behavior (OCB) and SMEs Performance. , there is not significant influence between budgetary on SMEs Performance, there is not significant effect between participation and SMEs Performance, there is not significant effect between budgetary on SMEs Performance. The novelty of this research is the relationship model of organizational citizenship behavior (OCB), budgetary, participation and information asymmetry to SMEs Performance During the Covid-19 Pandemic and VUCA Era